1987
DOI: 10.1177/154079698701200103
|View full text |Cite
|
Sign up to set email alerts
|

A Report on Competitive Employment Histories of Persons Labeled Severely Mentally Retarded

Abstract: The purpose of this article is to describe the competitive employment experiences of 21 persons labeled severely mentally retarded. Over an 8-year period from 1978 to 1986, 21 persons with measured intelligence levels under 40 were competitively employed with ongoing or intermittent job site support. A cumulative total of over $230,000 of unsubsidized wages was earned. Significant vocational problems included slow work rate and lack of appropriate social skills. The majority of the persons worked in part-time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…When Moore et al 24 examined outcomes of vocational rehabilitation case closures, they found that the vast majority of individuals with ID could be employed, including over half of individuals with severe ID. When individuals with severe ID are employed, ongoing support at the job site is usually needed, 25 but the Moore et al data do not make clear what percentage of those employed required SE arrangements. When individuals need ongoing support for employment, it is most likely to be provided through state programs for individuals with ID or developmental disability.…”
Section: Employment Outcomesmentioning
confidence: 98%
“…When Moore et al 24 examined outcomes of vocational rehabilitation case closures, they found that the vast majority of individuals with ID could be employed, including over half of individuals with severe ID. When individuals with severe ID are employed, ongoing support at the job site is usually needed, 25 but the Moore et al data do not make clear what percentage of those employed required SE arrangements. When individuals need ongoing support for employment, it is most likely to be provided through state programs for individuals with ID or developmental disability.…”
Section: Employment Outcomesmentioning
confidence: 98%
“…The largest cost to taxpayers resulting from funding supported employment involves the day-to-day operating expenditures of these programs Wehman, Hill, Wood, & Parent, 1987). These expenditures include job coach salaries, building maintenance, administrative costs, supplies, and numerous other expenses.…”
Section: Supported Employment Operating Costsmentioning
confidence: 99%
“…There is substantial documentation that adults with severe disabilities can achieve community employment (Kieraan & Stark, 1986;Rusch, 1986;Wehman, Hill, Wood, & Parent, 1987). The programs associated with these efforts have become known as supported employRequests for reprints should be sent to Jan Nisbet, PhD, University of New Hampshire, Institute on Disability, Morrill Hall, Durham, NH 03824-3595. ment programs.…”
mentioning
confidence: 97%